Sosialisasi dan Pengolahan Limbah Organik Menjadi Ekoenzim di Desa Maruat - Prasetyo, Rahadian Adi; Wahyuni, Indah; Usat Tebari Arleys, Andrew; Mevada Lumentah, Arnol; Aprisa Putri, Bunga; Arief Dwi Kesuma, Iqbal; Cahayani, Martita; Muhibbah Indriani, Nurul; Tri Andini, Winda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
One way to reduce pollution from organic waste is to produce ecoenzymes. The leading program of the KKN group of Mulawarman University Paser 02 Maruat Village is the socialization and processing of organic waste into ecoenzymes. The purpose of this activity is to raise public awareness of the importance of managing and utilizing organic waste to produce useful products. The method applied in this activity is through 2 stages, namely the preparation stage which contains an introduction to the importance of organic waste processing, and the implementation stage of the activity. The results of the training showed that training participants could understand the principles and processes of making ecoenzymes.